PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TYPE TPS (THINK PAIR SHARE) UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS VIIc MTS HUBBUL WATHAN BAGAN PUNAK TAHUN PELAJARAN 2015/ 2016 - Naldi Saputra; Darmadi '; Mariani Natalina Linggasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack:This reseach aims to improve learning outcomes of IPA class VIIc MTs Hubbul Wathan Bagan Punak in academic year 205/2016 through the implementation learning model cooperative type TPS. This research in March-April 2016. The research subjects is student class VIIc MTs Hubbul Wathan Bagan Punak totaling 28 people, consisting of 10 femele student and 18 male student. Parameter in research this is learning outcomes consisting of absorption, completeness learning, awerds group, learning activities student and teacher. The average absorption of studens in cycle I is 69.76% (enough), in cycle II average absorption student increased to 74.10% (good). completeness learning students individuals in cycle I is 90% (complete) and 10% (not complete). The cycle II increased to 100%. awerds group in cycle I consists of 4 group with super predicate and 3 groub with great, in cycle II all group received the predicate of greate. Average student activity in cycle I is 69.39% (enough) and in cycle II the average percentage of student activity increased to 75.50% (good). The average teacher activity in cycle I is 93,33% (very good) and in cycle II is 100% (very good). Of the results of this research note that the applicatiaon of learning models cooverative type TPS can improve student learning outcomes in the class VIIc MTs Hubbul Wathan Bagan Punak academic years 2015/2016.Keywords: learning cooperative, learning outcomes